(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Objective: The present study was aimed on developing and characterizing niosomal gels loaded with adrenergic agonist; dipivefrin HCl for prolonging precorneal residence time and improving bioavailability of drug for glaucoma treatment. Methods: Dipivefrin HCl niosomes were prepared using various non-ionic surfactants (span 20, span 60 and span 80) in the presence of cholesterol in different molar ratios by ether injection method. The selected formulations were incorporated into carbopol 934 and locust bean gum-based gels. Results: TEM studies confirmed that niosomes formed were white and spherical in shape and has a definite internal aqueous space with uniform particle size. Formulation F4 composed of span 60 and cholesterol (1:1) gave the highest entrapment (92.16±0.25%) and slower release results after 8 hours (Q8h=61.05±2.87%) among other formulations. The in-vitro drug permeation studies showed that there was a slow and prolonged release of drug from niosomal gel formulations as compared to niosomes itself. Considering the in-vitro release, niosomal gel formulation G2 were the best among the studied formulations. Gel formulation G2 showed higher spreadability (2.21±1.05 g.cm/s), higher bioadhesive strength (2314±1.29 dynes/cm2) but slower drug release (Q8h=52.13±1.81%) due to high gelling capacity. No sign of redness, inflammation, swelling or increased tear production was observed by Draize test. The IOP lowering activity of selected formulation was detected and compared with marketed Pilopine HS® gel. G2 formulation showed relative bioavailability 2.64 times more than bioavailability of marketed Pilopine HS® gel.